Peroxide alkaline for cleansing the baby bottle nipple to prevent oral thrush relaps - Maharani Laillyza Apriasari (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: Oral candidiasis is the most prevalent opportunistic infection affecting the oral mucosa. A number of predisposing factors have the capacity to convert Candida from the normal commensal flora to a pathogenic organism. Oral candidiasis is divided into primary and secondary infection. The primary infections are restricted to the oral and perioral sites, where as secondary infections are accompanied by sistemic mucocutaneous manifestation. Oral thrush is one of the candidiasis primary infection. Some presdiposing factors of oral thrush are neonatal, old people, or where oral microflora is disturbed by the treatment with broad spectrum antibiotics. Final diagnosis is determined by fungal culture examination, although through clinical examination oral thrush can be determined by swabbing the white pseudomembran. Purpose: This case report presents about the importance of using the antiseptic cleanser for baby bottle nipple to prevent oral thrush relaps and shows about peroxide alkaline as the alternatif of antiseptic cleanser for baby bottle nipple that can substitute chlorhexidine gluconat 0.2%. Case: A baby girl, 15 months old, when she was suffering influenza the pediatry gave amoxycillin 125 mg three times a day for ten days. Then the white plaque appeared on her dorsum of tongue. The therapy was Gentian Violet 1% four times a day for ten days was applied on dorsum of the tongue. The patient was suspected to suffer alergy reaction after using nistatin oral suspension four times a day had applied for 1 day. The instruction was doing sterilization for the baby bottle nipple in boiling water. Three days after the baby was cured, the white plaque was appeared on upper n lower lips mucous. Case management: The diagnosis was Oral thrush. The therapy was Gentian violet 1% four times a day for ten days that applied on upper and lower lips mucous. The instruction was doing the sterilization for baby bottle nipple in denture cleanser contain peroxide alkaline for five minutes, then it was washed with antiseptic soap, and soaked it in boiling water. Conclusion: The baby bottle nipple sterilization on the case of Oral thrush can not only by boiling in the water, but it must be keep in the antiseptic solution before boiled in the water. It was for preventing oral thrush relaps.Latar belakang: Kandidiasis rongga mulut merupakan infeksi opurtunistik yang sering terjadi pada mukosa mulut. Banyak faktor predisposisi yang menyebabkan Candida yang awalnya merupakan flora normal dalam rongga mulut berubah menjadi organisme patogen. Kandidiasis rongga mulut dibagi menjadi infeksi primer dan sekunder. Infeksi primer terjadi pada rongga mulut dan sekitarnya, sedangkan infeksi sekunder akan diikuti oleh manifestasi mukokutan secara sistemik. Oral thrush adalah salah satu dari infeksi primer candidasis. Beberapa faktor predisposisinya adalah pada bayi, orang tua atau microflora rongga mulut terganggu karena pemakaian jenis antibiotik spektrum luas. Diagnosis akhir didapatkan dari pemeriksaan kultur jamur, meskipun diagnosis dapat ditegakkan dengan pemeriksaan klinis melalui hapusan lesi pesudomembran putih. Tujuan: Laporan kasus ini tentang pentingnya penggunaan antiseptik untuk sterilisasi dot botol bayi untuk mencegah kekambuhan oral thrush dan menunjukkan alkalin peroxida sebagai alternatif bahan antiseptik untuk sterilisasi dot botol bayi, yang mampu mengganti Klorheksidin glukonat 0,2%. Kasus: Pasien adalah bayi perempuan usia 15 bulan, selama sakit batuk pilek mendapat obat dari dokter spesialis anak amoxycillin 125 mg yang diberikan 3 kali sehari selama 10 hari. Selanjutnya tampak plak putih pada lidah. Terapi yang diberikan adalah Gentian Violet 1% yang oleskan 4 kali sehari selama 10 hari pada dorsum lidah. Hal ini disebabkan pasien diduga mengalami alergi setelah diberi nistatin suspensi 4 kali sehari. Instruksi yang dianjurkan adalah menyeteril dot botol bayi dalam rebusan air. Setelah sembuh, 3 hari kemudian muncul lagi plak putih pada mukosa bibir atas dan bawahnya. Tatalaksana kasus: Pasien didiagnosis menderita oral thrush. Terapi yang diberikan adalah Gentian Violet 1% diaplikasikan 4 x 1 selama 10 hari pada mukosa bibir atas dan bawah. Instruksi yang diberikan adalah untuk menyeteril dot botol bayi dengan pembersih gigi tiruan yang mengandung alkalin peroksida selama 5 menit, kemudian dicuci dengan sabun mandi antiseptik, dan direbus dalam air. Simpulan: Sterilisasi pada bottle nipple pada pasien anak dengan oral thrush tidak dapat dilakukan dengan hanya merebus dalam air saja, melainkan harus merendam dengan cairan antiseptik terlebih dahulu sebelum direbus dalam air. Hal ini untuk mencegah terjadinya kekambuhan pada Oral thrush.